The Effect of Experiment-Based Discovery Learning Model on Psychomotor Learning Outcomes in Static Fluid Materials - Citron S. Payu (Postgraduate, University of Mataram, 2023)
This study aims to determine the differences in psychomotor learning outcomes of students using discovery learning models and problem-based learning (PBL) models in static fluid physics materials. The research location was conducted at SMAN 1 Boliyohuto for the 2021/2022 academic year in classes XI IPA type 1 and XI IPA type 2, each with 15 students. The research method used is quasi-experimental in the experimental class and the control class. The independent variable in this learning model is the discovery learning model. In contrast, the dependent variable is the results of students' psychomotor learning through observation sheets. Based on the analysis results, there were differences in student learning outcomes by applying the experimental-based discovery learning model to the PBL model. The control class scores were higher than the experimental class scores